Appropriation of feminist lexicon by the publicity discourse - Simão, Angélica Karim Garcia (2024)
In this work, we aim to identify the lexicon typical of the feministmovement, as well as its appropriation by Beauty Industry advertisement, madespecifically for women. In this way, we produced a corpus, named LEX-Fem, composedof texts incorporated in the feminist discussions, and, from the data collected, the lexicalitems considered representative of feminism were grouped in two lexical fields. Theselexical fields are based on “values wanted by feminists” and on “values criticized byfeminists”. From that, we grouped the lexical items in association spheres, in which theyrelate semantically, because their meanings are similar, in the context they were present.Besides, we present the analysis of one advertisement in which we verified the presenceof lexical items that can be considered part of the feminist lexicon because they establishsemantical relations to the defined association spheres